Short-range order kinetics in alpha-AgZn for various states of post-deformation defect annealing after cold-rolling - Migschitz, M.; Garlipp, W.; Pfeiler, W. (Elsevier B.V., 1996)
Kinetics of short-range ordering (SRO) in Ag with 21, 23 and 28 at% Zn is investigated by residual resistometry during isochronal and isothermal heat treatment for different states of post-deformation defect annealing after cold-rolling to about 30 and 60% thickness reduction. Resistivity changes due to pure ordering can be separated from the as-measured total resistivity change which includes defect annealing. Although the initial state of SRO of the as-rolled material can be estimated to be comparably low, for as-rolled and partially annealed states by appropriate thermal treatment evolution of SRO is achieved which corresponds quite well to that of recrystallized samples. It is observed, however, that quenched-in surplus vacancies contribute considerably to the ordering process for the recrystallized state and that this contribution is still increased by the grain growth during the final stage of annealing. It therefore turns out that SRO-kinetics under equilibrium vacancy conditions can be better observed in a state of post-deformation annealing, for which deformation induced point defects are annealed-out, but a relatively high dislocation density is still present to act as a vacancy sink. Copyright (C) 1996 Acta Metallurgica Inc.